The Influence And Impact of The Money Burning Strategy on The Future of Startups - Rachmad, Yoesoep Edhie (Adpebi Science Series, 2022)
The startup's goal to burn money is to generate brand awareness and generate loyalty. Startups will try to be the best in the eyes of consumers. Bubble burst is a phenomenon that occurs in the startup industry, which is quite horrendous and is the cause of mass layoffs. The purpose of this study is to analyze the money-burning strategy by startups and to find out the goals, benefits, impacts, and effects of the startup's money-burning strategy. Qualitative research using 111 startups in East Java. The results of this study (1) The money-burning marketing strategy is to promote by placing advertisements on social media such as Facebook, Instagram, TikTok, and Youtube, giving customers coupons, discounts, ultra-low price packages, profit points, and coins. (2) The impact of a cash-burning marketing strategy is the startup bubble bursting phenomenon, which has an impact on financial problems, layoffs, delays in the hiring process, and lower wages for employees. (3) The goal of a marketing strategy is to burn money, that is: to create awareness in the market and generate customer loyalty. (4) The benefits and reasons for a money- burning marketing strategy are: Accelerate company growth, survival in the industry, market acquisition strategies, and steps to kill competitors and attract new investors. (5) Companies that carry out a money-burning strategy are companies that invest in their future because the results cannot be seen immediately but require a time process. Companies must innovate by reading market signals and seeing which markets are growing.